2019
DOI: 10.1242/dev.174284
|View full text |Cite
|
Sign up to set email alerts
|

Defining developmental diversification of diencephalon neurons through single cell gene expression profiling

Abstract: The embryonic diencephalon forms integration centers and relay stations in the forebrain. Anecdotal expression studies suggest that the diencephalon contains multiple developmental compartments and subdivisions. Here, we utilized single cell RNA sequencing to profile transcriptomes of dissociated cells from the diencephalon of E12.5 mouse embryos. We identified the divergence of different progenitors, intermediate progenitors, and emerging neurons. By mapping the identified cell groups to their spatial origins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
3
19
0
Order By: Relevance
“…While these scenarios are not mutually exclusive, the latter may provide an attractive mechanism by which neurons could modulate the spatial distribution of astrocytes ( 13 ). Our clonal analyses reveal that neurons and sibling astrocytes originating from the same thalamic progenitor clone populate very similar territories, respecting boundaries among thalamic nuclei, extending earlier observations of the existence of nucleus-specific progenitor domains in the thalamus ( 26 , 27 , 36 ). Recent single-cell spatial transcriptomic mapping has revealed that in the cortex, astrocytes exhibit heterogeneity that does not follow neuronal layering ( 13 ).…”
Section: Discussionsupporting
confidence: 86%
“…While these scenarios are not mutually exclusive, the latter may provide an attractive mechanism by which neurons could modulate the spatial distribution of astrocytes ( 13 ). Our clonal analyses reveal that neurons and sibling astrocytes originating from the same thalamic progenitor clone populate very similar territories, respecting boundaries among thalamic nuclei, extending earlier observations of the existence of nucleus-specific progenitor domains in the thalamus ( 26 , 27 , 36 ). Recent single-cell spatial transcriptomic mapping has revealed that in the cortex, astrocytes exhibit heterogeneity that does not follow neuronal layering ( 13 ).…”
Section: Discussionsupporting
confidence: 86%
“…4 A , Extended Data Fig. 4-1 ) ( Guo Q, Li JYH, 2019 ; Huang KW, Sabatini BL, 2020 ; Huang et al, 2019 ; Huisman et al, 2019 ; Mizrak et al, 2020 ; Tepe et al, 2018 ; Van Hove et al, 2019 ; Wizeman et al, 2019 ). Generally, the Brs3 scRNA expression/nonexpression pattern matched that in the BRS3-Cre mice.…”
Section: Resultsmentioning
confidence: 99%
“… Datasets with fewer Brs3 -positive cells are listed. See studies by Saunders et al (2018) , Tepe et al (2018) , Guo and Li (2019) , Huang et al, 2019 ), Huisman et al (2019) , Van Hove et al (2019) , Wizeman et al (2019) , Huang and Sabatini (2020) , and Mizrak et al (2020) . Download .…”
Section: Resultsmentioning
confidence: 99%
“…The habenula controls reward- and aversion-driven behaviours by connecting cortical and subcortical regions with the monoamine system in the brainstem ( Benekareddy et al, 2018 ; Hikosaka, 2010 ). During postmitotic differentiation, thalamic and habenular neurons segregate into discrete nuclei ( Shi et al, 2017 ; Wong et al, 2018 ), develop a variety of subregional identities ( Guo and Li, 2019 ; Nakagawa, 2019 ; Phillips et al, 2019 ), extend axons toward their targets ( Hikosaka et al, 2008 ; López-Bendito, 2018 ) and acquire electrophysiological characteristics postnatally ( Yuge et al, 2011 ). The knowledge of the mechanisms that control postmitotic development in this region is important, because its functional dysconnectivity, which possibly originates from the period of postmitotic maturation, is implicated in schizophrenia, autism and other mental disorders ( Browne et al, 2018 ; Steullet, 2019 ; Whiting et al, 2018 ; Woodward et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%